the Hilir Ization And Marketing Of The Main Export Commodity Of Pulp : (A Value Chain Approach) - Asrilis Saban; Muhammad Ivan Vadilaksono; Rusyqy Fuad Arsa Barus; Sahara Sahara (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (ADPEBI), 2022)
The aims of this paper are 1) to map the production of upstream and downstream pulp commodities. 2) knowing the potential and impact of downstreaming on regional and national economic growth. 3) formulate a recommendation for the development strategy of the main commodity downstream. The data used is secondary data, namely Riau Province Input-Output data in 2016 with a 52 x 52 matrix. Data obtained from the Central Statistics Agency (BPS). The analytical method used isAnalysis (IO) ofbackward linkage and forward linkagefrom the rubber plantation sector as a provider of inputs and users of inputs as well as the impact on the economy in Riau Province. The results showed thatProduction from upstream to downstream of pulp commodities can be divided into several industries, including the forestry and logging sector, the textile industry sector, the paper industry sector or paper goods, printing, and recording media reproduction. The sector with the most potential and impact on economic growth from downstreaming of pulp commodities is the paper and paper goods industry, printing, and recording media reproduction. Strategies that can be taken to develop the paper and paper goods industry, printing, and reproduction of recording media are increasing economies of scale in production, determining appropriate market segments, increasing product value (increasing value), and maintaining economic stability.